International Financial Statistics, May 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This May 2015 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. Quarterly issues of Direction of Trade Statistics (DOTS) provide, for 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The yearbook provides, for the most recent seven years, detailed trade data by country for approximately 184 countries, the world, and major areas. The combined subscription package includes all issues of IFS, DOTS, Government Finance Statistics Yearbook, and Balance-of-Payments Statistics Yearbook.